2016
DOI: 10.1021/acs.jpcb.5b12667
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions of PYR14-TFSI as a Function of Pressure and Temperature: the Competition between Smaller Volume and Lower Energy Conformer

Abstract: A detailed Raman study has been carried out on the ionic liquid 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (PYR14-TFSI) over a wide pressure (0-8 GPa) and temperature (100-300 K) range. The explored thermodynamic region allowed us to study the evolution of the system across different solid and liquid phases. Calculated Raman spectra remarkably helped in the spectral data analysis. In particular, the pressure behavior of the most intense Raman peak and the shape analysis of the ruby fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 39 publications
5
64
0
Order By: Relevance
“…All bands shift to higher wavenumbers with increasing pressure, as expected. After pressurization to 1 GPa, one can note the absence of the spectral line that, at room pressure, is centered around 327 cm −1 , due to cis ‐TFSI . This finding is consistent with infrared spectroscopy measurements performed on TMPA‐TFSI, which indicated that between 0.1 and 0.2 GPa, the system crystallizes into a structure containing trans ‐TFSI only …”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…All bands shift to higher wavenumbers with increasing pressure, as expected. After pressurization to 1 GPa, one can note the absence of the spectral line that, at room pressure, is centered around 327 cm −1 , due to cis ‐TFSI . This finding is consistent with infrared spectroscopy measurements performed on TMPA‐TFSI, which indicated that between 0.1 and 0.2 GPa, the system crystallizes into a structure containing trans ‐TFSI only …”
Section: Resultssupporting
confidence: 86%
“…The Raman spectrum of MIX98‐2 measured at 0 and 1 GPa, after overnight equilibration of the pressure, is shown in Figure . Among the bands centered in the wavenumber range between 260 and 350 cm −1 , four of them shift to higher wavenumbers as the pressure is increased (285, 301, 319, and 345 cm −1 ) whereas the band centered at 326 cm −1 at ambient pressure ascribed to cis ‐TFSI completely disappears. This behavior suggests that MIX98‐2, similarly to the pure TMPA‐TFSI compound, crystallizes upon compression into a structure containing only trans ‐TFSI.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations